Effects of annealing temperature on the structural, mechanical and electrical properties of flexible bismuth telluride thin films prepared by high-pressure RF magnetron sputtering - Kamolmad Singkaselit; Aparporn Sakulkalavek; Rachsak Sakdanuphab (My University, 2017)
In this work BixTey thin films were deposited on polyimide substrate by a high-pressure RF magnetron sputtering technique. The deposited condition was maintained using a high pressure of 1.3 × 10−2 mbar. The as-deposited films show Bi2Te3 structure with Te excess phase (Te-rich Bi2Te3). After that, as-deposited films were annealed in the vacuum chamber under the N2 flow at temperatures from 250 to 400 °C for one hour. The microstructure, cross-section, [Bi]:[Te] content, and the mechanical, electrical and thermoelectric properties of as-deposited and different annealed films were investigated. It was found that the annealing temperature enhanced the crystallinity and film density for the temperature range 250–300 °C. However, the crystal structure of Bi2Te3 almost changed to the BiTe structure after annealing the films above 350 °C, due to the re-evaporation of Te. Nano-indentation results and cross-section images indicated that the hardness of the films related to the film density. The maximum hardness of 2.30 GPa was observed by annealing the films at 300 °C. As a result of an improvement in crystallinity and phase changes, the highest power factor of 11.45 × 10−4 W m−1K−2 at 300 °C with the carrier concentration and mobility of 6.15 × 1020 cm−3 and 34.03 cm2 V−1 s−1, respectively, was achieved for the films annealed at 400 °C.
Keywords: Bismuth telluride; Advanced Thermoelectric Materials and Devices